DEGRADASI EKOSISTEM RAWA PESISIR DI KECAMATAN JORONG KABUPATEN TANAH LAUT KALIMANTAN SELATAN - Eka Iriadenta (Fish Scientiae, 2019)
Decreasing area of coastal swamp ecosystem causing stress to aquatic biota whichliving in those habitat, and give impact to fishermen’s prosperity level. Study of coastal swamp’s condition really important, with aim as consideration to decide policies that needed to reach environmental balancing and sustainibility of exploitation. Study was done to both primary and secundary data, which include tabulative, graphical, qualitative and quantitative/statistics and computative, both description and inferential, and so spatial analysis for reach locally information of mangrove area’s degradation, and temporal information of comparation with secondary data. Condition of ecosystem of coastal swamp in Jorong subdistrict, which representated by condition of ecosystem of mangrove showing damaged to really damaged condition. Rate of decreasing of mangrove areas in Jorong subdistrict reach of 614,49 ha, or average rate of areas decreasing were 38,41 ha/year. Factors that caused damaged/degradation process of coastal swamp in Jorong subdistrict, Tanah Laut Regency dominated by wave activities and area’s converted.